Peran Hukum Administrasi Dalam Pengendalian Izin Lingkungan: Studi Kasus Proyek Strategis Nasional - Bilqisya, Azra; Atia, Tia; Salsabila, Hera (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Environmental permit control in national strategic projects (PSN) plays a crucial role in maintaining the balance between development and environmental protection. Administrative law is essential in regulating licensing mechanisms, ensuring compliance with regulations, and mitigating negative impacts on ecosystems and surrounding communities. This article discusses administrative law concepts, environmental permit issuance procedures, and the role of government institutions, including the Ministry of Environment and Forestry and local governments, in supervision and law enforcement. Case study analysis of several PSNs reveals legal challenges such as transparency, accountability, and conflicts of interest frequently encountered in the permitting process. Additionally, policy implications for project sustainability and community welfare are examined. By considering legal and social aspects, this article offers recommendations to enhance the effectiveness of environmental permit administration through policy reforms, strengthened oversight, and increased public participation. This research provides insights for improving PSN permitting systems to ensure sustainable development while aligning with environmental protection principles.